Progress in Microwave-Assisted Synthesis of Quantum Dots (Graphene/Carbon/Semiconducting) for Bioapplications: A Review - Singh, D (Elsevier Ltd, 2019)
Quantum dots (QDs) are small nanometer-sized (<10 nm) pure or composite materials with excellent novel properties, thus making them interesting and emerging candidates for new and exceptional applications in biomaterials research fields. As emerging members of QDs, carbon (especially, carbon QDs and graphene QDs) and semiconducting QDs have attracted greater attention owing to their excellent properties, unique size, versatile surface, and biocompatibility with nanotechnology. In this work, a comprehensive overview on the possibilities and achievements in the field of carbon and semiconducting QDs obtained by only microwave (MW)-assisted for biomedical purposes is provided. This specific literature review provides knowledge about MW-assisted synthesis and some selected bioapplication of carbon and semiconducting QDs. Currently, the MW-assisted fabrication of QDs represents a growing research field in nanomaterial research. MW-assisted approach for QD synthesis has been studied in details as this approach has several advantages such as uniform distribution of energy inside the reaction vessel, shorter reaction times, environmentally friendly and energy-saving technique, high reproducibility, and excellent control over experimental parameters. Also, a comprehensive overview is provided in this review, which contains the possibilities and achievements using MW-assisted heating approaches. This article updates the latest synthesis progress as well as applications and also comments all the challenges and perspective in this emerging research area. © 2019 Elsevier Ltd